2020
DOI: 10.1017/s0022109020000277
|View full text |Cite
|
Sign up to set email alerts
|

Internal Labor Markets, Wage Convergence, and Investment

Abstract: I document wage convergence in conglomerates using detailed plant-level data: Workers in low-wage industries collect higher-than-industry wages when the diversified firm also operates in high-wage industries. I confirm this effect by exploiting the implementation of the North American Free Trade Agreement (NAFTA) and changes in minimum wages at the state level as sources of exogenous increases in wages in some plants. I then track the evolution of wages of the remaining workers of the firm, relative to workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…This literature has shown that firm boundaries matter for capital and R&D allocation (Seru, 2014;Giroud and Mueller, 2015). A large body of work has presented evidence that is consistent with a cross-subsidization pattern in investment and labor (Shin and Stulz, 1998;Rajan, Servaes and Zingales, 2000;Stein, 1997;Ozbas and Scharfstein, 2009;Silva, 2016), though several papers argue against such evidence (Chevalier, 1999;Maksimovic and Philips, 2001;Whited, 2001;Çolak and Whited, 2007;and Custódio, 2014). Our paper extends this literature by suggesting that organization structure may itself be designed to foster the ability of firms to use internal capital markets when these are most valuable.…”
Section: Introductionmentioning
confidence: 54%
“…This literature has shown that firm boundaries matter for capital and R&D allocation (Seru, 2014;Giroud and Mueller, 2015). A large body of work has presented evidence that is consistent with a cross-subsidization pattern in investment and labor (Shin and Stulz, 1998;Rajan, Servaes and Zingales, 2000;Stein, 1997;Ozbas and Scharfstein, 2009;Silva, 2016), though several papers argue against such evidence (Chevalier, 1999;Maksimovic and Philips, 2001;Whited, 2001;Çolak and Whited, 2007;and Custódio, 2014). Our paper extends this literature by suggesting that organization structure may itself be designed to foster the ability of firms to use internal capital markets when these are most valuable.…”
Section: Introductionmentioning
confidence: 54%
“…We indeed show in Supplemental Appendix H.5 that wage differences across locations among plants within the same multi‐plant firm are smaller than wage differences among all plants across those locations. See Silva (2020) for further evidence of fairness norms in multi‐plant firms and Hjort, Li, and Sarsons (2020) for further evidence of firm‐wide wage setting procedures.…”
mentioning
confidence: 99%
“…Our paper also contributes to the literature on the internal labor markets of conglomerates with fully-owned subsidiaries or plants (Giroud and Mueller 2015;Tate and Yang 2015;Silva 2017). Although similar mechanisms apply to both conglomerates and business groups, a key difference is that worker flows are within a firm in conglomerates and between firms in business groups.…”
Section: Introductionmentioning
confidence: 90%